Vascular Endothelium at the Molecular Level: From Fundamental Knowledge Toward Medical Implementation - Vladimir P. Shirinsky (Biomedicines)
The concept of multiple physiologic roles played by a single layer of endothelium on the intimal face of blood vessels started gaining recognition in the 1960s [...]